Labour Migration in Europe Volume I Integration and Entrepreneurship among Migrant Workers - A Long-Term View (Springer International Publishing, 2018)
In this book, Fauri and Tedeschi bring together contributions that outline the movement of job seekers and ethnic minority entrepreneurs in Europe, all with the aim of analysing the overall impact of different forms of migration on European economies in the last hundred years. Contributions address a broad range of themes, from the motivations of migrants and the process of their integration into their destination country, to their overall social and economic impact onto said country at a structural level. In addressing questions as to why some ethnic groups seem to compete more successfully in business, as well as addressing questions about how skilled labour can be attracted and retained, this volume forms part of a very important multidisciplinary dialogue on labour migration. The policy implications of answering such questions are also discussed, as contributors ultimately examine whether skills-dependent migration policy needs to be form part of a common strategy, either at a national or an international level. Francesca Fauri is Associate Professor of Economics at the University of Bologna, Italy. She won a Jean Monnet Chair on European Migration History in 2016 and has published extensively on issues concerning the history of European economic integration and European economic and migration history. Paolo Tedeschi is Associate Professor in Economic History at the University of Milan-Bicocca, Italy. He has taught at the UC Louvain, Belgium, and the University of Luxembourg, Luxembourg. His research and publications focus on the history of European integration from the origin to the Euro.